Subsurface damage in alumina and alumina-silicon carbide nanocomposites - Tanner, B; Wu, H; Roberts, S; Hase, T (2004)
The subsurface plastic deformation below alumina (Al 2O 3) and Al 2O 3-silicon carbide (SiC) nanocomposite surfaces subjected to grinding, polishing and annealing has been measured by high-resolution grazing-incidence parallel-beam X-ray powder diffraction and transmission electron microscopy. The variation with angle in the full width at half-height maximum (FWHM) of the X-ray Bragg peaks was successfully modelled by a FWHM distribution that fell exponentially with increasing depth. Consistent parameters were extracted from data taken using both prism and pyramidal reflecting planes. Correlation was found between the depth at which the FWHM fell to 1/e of the surface value and the depth of damage observed by transmission electron microscopy. The associated surface strain in the nanocomposite was found to increase linearly with increasing diameter of the diamond polishing particles. In ground 5 vol.% SiC nanocomposite, these random surface strains fell by a factor of 7 and the depth of damage increased by a factor of 3 after annealing at 1250°C for 2 h. No differences were observed in the Bragg peak FWHM as a function of angle for material polished with 1 μm diamond grit before and after annealing.